The influence of early serum heparin-binding protein (HBP) levels on the occurrence of sepsis in patients with severe burns: HBP levels on occurrence of sepsis in patients with severe burns - Xiang, Lihan; Yang, Guimei; Lou, Liming; Lv, Le; Zheng, Liyuan; Zhang, Caixia; He, Qian (Journal of Medical Biochemistry, 2025)
[Objective] To evaluate the expression levels of early serum heparin-binding protein (HBP) in patients with severe burns and investigate its prognostic significance and predictive utility for sepsis development.[Methods] The clinical data of 52 patients with severe burns who were admitted to our hospital between January 2023 and May 2025 were retrospectively analyzed. General information, including the patient's age, sex, body mass index (BMI), total burn area, and tracheal intubation or tracheotomy, was collected. Within 48 hours of the patient's admission, the patient's blood pressure, white blood cell count, serum procalcitonin (PCT), and serum C reactive protein (CRP) level were measured. The second assessment of acute physiology and chronic health within 48 hours of admission included the results of the sequential organ failure assessment (SOFA) and APACHE II. The patients were separated into two groups on the basis of their conditions at discharge: the nonsurviving group and the surviving group.[Results] Compared with the nonsepsis group (8.2 ng/mL), the sepsis group had a considerably greater median early serum HBP level (20.8 ng/mL) (P14.6 ng/mL was an independent risk factor for the development of sepsis (OR=4.53, 95% CI: 2.67–7.69). According to survival analysis, patients in the high-HBP group had a significantly greater 28-day mortality rate (log-rank P
Keywords: Heparin-binding protein (HBP); Severe burn; Sepsis; Early warning index; Survival prognosis